2003
DOI: 10.1007/s00280-003-0644-6
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of weekly paclitaxel, 13- cis -retinoic acid, and interferon alpha in patients with prostate cancer and other advanced malignancies

Abstract: This is the first study in which the safety and clinical activity of weekly TAX combined with CRA/IFN has been demonstrated. The assessment of PBMC bcl-2 is feasible in this weekly chemotherapy schedule

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The over-expression of Bcl-2 is implicated as a cause of hormonal and chemotherapy resistance and has been shown to increase with castration in prostate cancer [3,4]. Prior studies conducted by our group and other investigators demonstrated that retinoids can decrease expression of Bcl-2, that the combination of 13-cis retinoic acid (CRA) and interferon (IFN) enhanced the effect of paclitaxel chemotherapy, and that the combination can be safely administered in phase I studies [5-7]. More recently, our group and other investigators have studied novel BH3 domain mimetics such as AT101 and ABT263, which modulate multiple Bcl-2 family proteins, and are being tested in early clinical studies [8-10].…”
Section: Introductionmentioning
confidence: 99%
“…The over-expression of Bcl-2 is implicated as a cause of hormonal and chemotherapy resistance and has been shown to increase with castration in prostate cancer [3,4]. Prior studies conducted by our group and other investigators demonstrated that retinoids can decrease expression of Bcl-2, that the combination of 13-cis retinoic acid (CRA) and interferon (IFN) enhanced the effect of paclitaxel chemotherapy, and that the combination can be safely administered in phase I studies [5-7]. More recently, our group and other investigators have studied novel BH3 domain mimetics such as AT101 and ABT263, which modulate multiple Bcl-2 family proteins, and are being tested in early clinical studies [8-10].…”
Section: Introductionmentioning
confidence: 99%
“…Bcl-2 is an antiapoptotic protein that is overexpressed in multiple tumors including prostate cancer, thereby conferring resistance to therapies that induce apoptosis, such as ADT [3, 4]. Based upon preclinical data suggesting that the efficacy of ADT could be enhanced by combing ADT with AT-101, we undertook the current single arm phase II study in men with newly diagnosed hormone sensitive metastatic disease in order to determine if the combination could improve upon a novel clinical endpoint in this disease setting, the rate of patients achieving an undetectable PSA after 7 months of ADT and AT-101.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies in prostate cancer tissue demonstrated that Bcl-2 is over-expressed in most patients with castration-resistant prostate cancer (CRPC) [3, 4]. In animal models, Bcl-2 is responsible for drug resistance to chemotherapy and ADT, and modulation of Bcl-2 improves sensitivity [5, 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the use of cytokines in prostate cancer treatment, interferon-alpha is a cytokine that has been demonstrated to have antiproliferative effects against prostate cancer cells in vitro [ 160 ]. The combination of cis-retinoic acid and interferon-alpha has been explored as a potential treatment for prostate cancer [ 161 ]. In vitro studies have shown that interferon-alpha, with or without cis-retinoic acid, has antiproliferative effects against prostate cancer cell lines: prostate adenocarcinoma cell line 3 (PC3) and Daudi lymphoblastoid cell line-145 (D-145) [ 160 ].…”
Section: Other Immune-based Therapiesmentioning
confidence: 99%